PENGARUH JUMLAH UANG BEREDAR, SUKU BUNGA DAN NILAI TUKAR RUPIAH TERHADAP INFLASI DI INDONESIA PERIODE 2018-2021 - Novita Nurcahyani; Deny Yudiantoro (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine the effect of the money supply, interest rates and the rupiah exchange rate on inflation in Indonesia for the 2018-2021 period. The method used is a quantitative research method. The sampling technique in this study was carried out by purposive sampling and macro time series data published by Bank Indonesia during the 2018-2021 period covering data on the money supply, interest rates and exchange rates for the monthly period. The results of the study, namely based on the F test, showed that the model used in the study was correct with a significant level below 0.05, namely 0.000. This shows that the variables of the money supply, interest rates and exchange rates if tested simultaneously or together have a positive and significant effect on inflation. The t-test shows that the money supply and the rupiah exchange rate have no effect on inflation with a significance value of 0.741 and 0.052, respectively, while interest rates affect inflation with a significance value of 0.008 0.05. The money supply, interest rates and rupiah exchange rate affected inflation by 59.6%.